2016
DOI: 10.2217/pgs.16.12
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine S -Methyltransferase Testing for Averting Drug Toxicity in Patients Receiving Thiopurines: a Systematic Review

Abstract: Clinical decision-makers require high-quality evidence of clinical validity and clinical utility of TPMT genotyping to ensure appropriate use in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…There is an ongoing debate about the advantages and disadvantages of a genotyping vs phenotyping approach, which is discussed in depth in other publications. 63,72 It is important to note that blood transfusions in a 3-month time interval before TPMT phenotyping might affect the analyses and yield unreliable results. Despite observational studies reporting significantly higher risk of myelosuppression in a subset of patients treated with thiopurines, the quality of evidence supporting routine TPMT testing to guide thiopurine dosing was deemed low based on RCTs.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…There is an ongoing debate about the advantages and disadvantages of a genotyping vs phenotyping approach, which is discussed in depth in other publications. 63,72 It is important to note that blood transfusions in a 3-month time interval before TPMT phenotyping might affect the analyses and yield unreliable results. Despite observational studies reporting significantly higher risk of myelosuppression in a subset of patients treated with thiopurines, the quality of evidence supporting routine TPMT testing to guide thiopurine dosing was deemed low based on RCTs.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…The calculated sensitivity to detect a homozygous or heterozygous mutation ranged from 13.4% to 100.0% and the calculated specificity ranged from 90.9% to 100.0%. 29 A previous systematic review by Donnan et al reported ranges for the sensitivity and specificity of the TPMT genotype test of 55-100% and 94-100%, respectively. The TPMT phenotype test sensitivity and specificity ranged from 92% to 100% and from 86% to 98%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…29 Eligible studies were those that: (1) evaluated either a TPMT genotype or TPMT phenotype technology in comparison to a reference standard; (2) presented results on the sensitivity and specificity or positive/negative predictive values together with prevalence, or allowed these measures to be calculated from data in the text, in supplemental files, or from data obtained from study authors; (3) were conducted in any age group; (4) were conducted in any disease group; and (5) were published in any language, so long as translation was possible. Studies not conducted in humans, including animal, tissue and in vitro studies were excluded.…”
Section: Study Selectionmentioning
confidence: 99%
“…Targeted panels may also include genes in drug metabolism. Including genes such as TMPT and NUDT15 on a hematological cancer panel can provide crucial genotype information that clinicians may use to alter thiopurine dosing, reducing medication toxicity [Burnett et al, 2014;Yang et al, 2015;Roy et al, 2016].…”
Section: Detection Of Underlying Germline Variantsmentioning
confidence: 99%